Failure of the proximal locking compression plate in treatment of trochanteric femoral fractures - Polivoda, Oleksandr; Chabanenko, Diomyd (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2019)
Treatment of proximal femoral fractures constantly draw attention of trauma surgeons because of their greater incidence. Last 10 years, shows the prevalence of intramedullary techniques, however plate osteosynthesis with proximal locking plate is still quite common in everyday practice. Objective: to conduct a retrospective analysis of treatment results of patients with proximal femoral fractures operated with locking proximal femoral plate and to identify the main mechanisms causing the high rate of unsatisfactory results. Methods: the study included 21 patients (mean age (65 ± 12) years) with fractures 31А2 and 31А3 according to the AO classification, that undergone osteosynthesis with proximal femoral LCP plate. Mean follow-up period was 7.5 months after surgery. Results: the absence of displacement and initial consolidation of the fracture was achieved in 17 of 21 patients (80.9 %). The average time of union was 6 months. Unsatisfactory results of treatment were observed in 4 cases (19.1 %). All of them were associated with fracture of the plate and nonunion of bone fragments. The fracture of the plate occurred at the level of the distal 7.3 mm locking hole in 8–9 months after the surgical intervention. In all this cases the revision surgery- implantation of proximal femoral antirotational nail (PFNA) was performed. In our opinion, such a large number of unsatisfactory results associated with excessive rigidity and an undesirable concentration of load. Conclusions: usage of proximal plates with angular stability of the screws is not always effective for the treatment of unstable fractures of the proximal femur. The high frequency of unsatisfactory results that required re-osteosynthesis with the PFNA, indicates the need for careful preoperative planning and selection of stabilization method for proximal femoral fracture treatment.